Lysosomal integral membrane protein-2 (LIMP-2/SCARB2) is involved in lysosomal cholesterol export - Heybrock, Saskia; Kanerva, Kristiina; Meng, Ying; Ing, Chris; Liang, Anna; Xiong, Zi-Jian; Weng, Xialian; Ah Kim, Young; Collins, Richard; Trimble, William; Pomès, Régis; Privé, Gilbert G.; et al. (Nature communications, 2019)
The intracellular transport of cholesterol is subject to tight regulation. The structure of the lysosomal integral membrane protein type 2 (LIMP-2, also known as SCARB2) reveals a large cavity that traverses the molecule and resembles the cavity in SR-B1 that mediates lipid transfer. The detection of cholesterol within the LIMP-2 structure and the formation of cholesterol − like inclusions in LIMP-2 knockout mice suggested the possibility that LIMP2 transports cholesterol in lysosomes. We present results of molecular modeling, crosslinking studies, microscale thermophoresis and cell-based assays that support a role of LIMP-2 in cholesterol transport. We show that the cavity in the luminal domain of LIMP-2 can bind and deliver exogenous cholesterol to the lysosomal membrane and later to lipid droplets. Depletion of LIMP-2 alters SREBP-2-mediated cholesterol regulation, as well as LDL-receptor levels. Our data indicate that LIMP-2 operates in parallel with Niemann Pick (NPC)-proteins, mediating a slower mode of lysosomal cholesterol export. Cholesterol transport is tightly regulated in the cell and in lysosomes is regulated by NPC1/2. Here, Heybrock et al. use molecular modeling, knockout mice and cell based studies to show that LIMP-2 also mediates lysosomal cholesterol transport.